ANALISIS ENAM FAKTOR PREVENTIF PERILAKU SEKSUAL BERISIKO REMAJA SEKOLAH MENENGAH PERTAMA GENERASI PLATINUM - Arthur Huwae (Program Studi S1 Psikologi, 2020)
ABSTRACT. The risk-taking issue of sexual behavior at a young age often leads to bad damage for the teenager and its surroundings when viewed as an asset of a nation to engage in such an aspect of development, the preoccupation of sexual behavior must be overcome by involving a number of important factors among famlies, school, peers, religiousity, social media, and local cultural values. The aims of the discussion, then is to recognize the simultaneous impact of six preventive factors : risky sexual behavior on the teenager, and individual relationships with adolescent risky sexual behavior. The methods used are double-regression quantitative and the correlation by Karl Pearson. Participant engaged by 150 students (sevent – nine grade) with saturated technique sampling. The scales that used are the parent-adolescent relationship scale (Hair, dkk., 2005), quality of school life scale (Eptein dan McPartland, 1998), CAYCI peer relationship scale : middle/high school student version (Butcher, dkk., 2016), the adolescent religious coping scale (Bjorck, 2009), outside and inside school media of behavior scale (Lu, dkk., 2018), cultural intelligence scale (Earley dan Ang, 2003), and the scale of risky sexual behavior. The result of the research hypothesis is accepted, which means there are simultaneous effect of six factors on adolescent risky sexual behavior with a value of 9,179 and of significance = 0,000, and there is a significant negative relationship between each factor and the risky sexual behavior of adolescents. The value of the six preventive factors is in high categroies, and the risky sexual behavior of adolescents is in a low category. This result indicates that six specific factors can be established as a primary mediator incoping with sexual behavior at risk for the adolescence of the platinum generation